Impacto de las nanopartículas de Óxido de Cerio en el tratamiento de aguas residuales (Jóvenes en la Ciencia, 2024)
products such as personal care products. This increase in their demand and production hasgenerated the accumulation of these nanomaterials in some environmental receptors, such as water;An example of this is the biological processes for wastewater treatment. That, is why in the presentstudy the evaluation of the impact of cerium oxide nanoparticles in a biological system that used amicroalgae-bacteria consortium for the removal of carbon, nitrogen and phosphorus, finding thatthere were no nanoparticles in the wastewater treatment process.